Peripheral Artery Disease: Past, Present, and Future - Campia, Umberto; Gerhard-Herman, Marie; Piazza, Gregory; Goldhaber, Samuel Z (The American journal of medicine, 2019)
Peripheral artery disease is a prevalent but underdiagnosed manifestation of atherosclerosis. There is insufficient awareness of its clinical manifestations, including intermittent claudication and critical limb ischemia and of its risk of adverse cardiovascular and limb outcomes. In addition, our inadequate knowledge of its pathophysiology has also limited the development of effective treatments, particularly in the presence of critical limb ischemia. This review aims to highlight essential elements of the epidemiology and pathophysiology of peripheral artery disease, bring attention to the often-atypical manifestations of occlusive arterial disease of the lower extremity, increase awareness of critical limb ischemia, briefly describe the diagnostic role of the ankle brachial index, and go over the contemporary management of peripheral artery disease. An emphasis is placed on evidence-based medical treatments to improve symptoms and quality of life and to reduce the risk of cardiovascular and limb events in these patients, including supervised exercise training, smoking cessation, antagonism of the renin-angiotensin system, lipid-lowering, antiplatelet, and antithrombotic therapies.